Cover Feature: Understanding the Effect of Polydopamine Interlayer on the Long‐Term Cycling Performance of Silicon Anodes: A Multiphysics‐Based Model Study (Batteries & Supercaps 6/2019). Issue 6 (31st May 2019) - Appiah, Williams A.; Kim, Dohwan; Song, Jihun; Ryou, Myung‐Hyun; Lee, Yong M.
Abstract : The Cover Feature highlights the use of a physics‐based model to unveil the positive and negative impact of a polydopamine interlayer (brown surface) on the electrochemical performance of silicon‐based lithium‐ion batteries. The polydopamine interlayer enhances the adhesion strength between the silicon composite electrode (blue balls) and copper current collector (substrate) as confirmed by SAICAS. More information can be found in the Article by W. A. Appiah et al .